Impact of humanities and social sciences curriculum in an undergraduate medical education programme - Ghias, Kulsoom; Khan, Kausar; Ali, Rukhsana; Azfar, Shireen; Ahmed, Rashida (Journal of the Pakistan Medical Association, 2020)
To evaluate the impact of humanities and social sciences curriculum in an undergraduate medical education programme. The qualitative study was conducted from May 2016 to May 2017 at a private medical college in Karachi where humanities and social sciences subject is an art of the undergraduate curriculum as a 6-week module at the start of Year 1 of the five-year programme. Focus group discussions were held with students from all the five years as well as with faculty related to humanities and social sciences, basic sciences and their clinical counterparts. The views of alumni of the undergraduate programme who are now members of the faculty at the institution were also explored and semi-structured interviews were conducted with institutional academic leaders. MAXQDA software was used to identify the themes for analysis. Of the 50 participants, 27(54%) were students, 21(42%) were faculty members and 2(4%) were academic leaders. From the 11 sub-themes, 5 themes were identified: Expectations, Strengths, Challenges, Way forward, and Institutional role and responsibility. Faculty members perceived humanities and social sciences as encouraging creative and critical thinking, boosting students' confidence and positively impacting their behaviour. Student perception seemed to change as they progressed through the years and they appreciated its impact at different stages. The existing humanities and social sciences curriculum can be further strengthened by integrating contents throughout the five-year programme and continuing it as a longitudinal theme rather than limiting it to a one-time exposure at the start of the programme.